2018
DOI: 10.1038/s41612-018-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

Similar spatial patterns of global climate response to aerosols from different regions

Abstract: Anthropogenic aerosol forcing is spatially heterogeneous, mostly localised around industrialised regions like North America, Europe, East and South Asia. Emission reductions in each of these regions will force the climate in different locations, which could have diverse impacts on regional and global climate. Here, we show that removing sulphur dioxide (SO 2 ) emissions from any of these northern-hemisphere regions in a global composition-climate model results in significant warming across the hemisphere, rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 41 publications
6
61
1
Order By: Relevance
“…The precipitation responses in the individual experiments also positively correlate with that from the NML experiment (Figure S2). Following a similar line of thought, it suggests that there is a preferred response of large‐scale precipitation to aerosols from different regions (Dong et al, ; Kasoar, ; Kasoar et al, ).…”
Section: Resultsmentioning
confidence: 79%
“…The precipitation responses in the individual experiments also positively correlate with that from the NML experiment (Figure S2). Following a similar line of thought, it suggests that there is a preferred response of large‐scale precipitation to aerosols from different regions (Dong et al, ; Kasoar, ; Kasoar et al, ).…”
Section: Resultsmentioning
confidence: 79%
“…The strongest cooling occurs locally to the region of forcing. Similarly, Kasoar et al () found that when SO 2 emissions are removed from specific regions, the temperature response does tend to be strongest local to the forcing, but there is also a common broad pattern response regardless of forcing location. The particularly strong cooling over Europe for 10×SO4eur is consistent with high‐latitude forcing being less effectively damped by radiation (Kang & Xie, ).…”
Section: Resultsmentioning
confidence: 91%
“…The strong regional variations in aerosol distributions and ERF may matter for determining impacts of aerosol ERF on several aspects of the Earth system (e.g. Bollasina et al, 2011;Chung and Soden, 2017;Kasoar et al, 2018), but those considerations are also not addressed in this review. Both RF and ERF are measured in W m −2 and cover both the solar (shortwave, SW) and terrestrial (longwave, LW) parts of the electromagnetic spectrum.…”
Section: Scope and Definitionsmentioning
confidence: 99%